1997
DOI: 10.1074/jbc.272.42.26271
|View full text |Cite
|
Sign up to set email alerts
|

Modification of α-Chain or β-Chain Heme Pocket Polarity by Val(E11) → Thr Substitution Has Different Effects on the Steric, Dynamic, and Functional Properties of Human Recombinant Hemoglobin

Abstract: The dynamic and functional properties of mutant deoxyhemoglobins in which either the ␤-globin Val 67 (E11) or the ␣-globin Val 62 (E11) is replaced by threonine have been investigated through the thermal evolution of the Soret absorption band in the temperature range 300 to 20 K and through the kinetics of CO rebinding after flash photolysis at room temperature. The conformational properties of the modified ␣ chain and ␤ chain distal heme pockets were also studied through x-ray crystallography and molecular mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…As previously discussed, the Val 3 Thr substitution does not modify the steric characteristics of the heme pocket (7,10,11); therefore, this system represents an excellent model to investigate the effect of modified heme pocket polarity on the ligand binding parameters and their correlation with IR spectroscopy. For this analysis, the kinetic curves have been analyzed in terms of two exponentials of equal amplitudes (describing the contributions from ␣-and ␤-subunits).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…As previously discussed, the Val 3 Thr substitution does not modify the steric characteristics of the heme pocket (7,10,11); therefore, this system represents an excellent model to investigate the effect of modified heme pocket polarity on the ligand binding parameters and their correlation with IR spectroscopy. For this analysis, the kinetic curves have been analyzed in terms of two exponentials of equal amplitudes (describing the contributions from ␣-and ␤-subunits).…”
Section: Resultsmentioning
confidence: 95%
“…From Fig. 3, it can be seen that, at variance with the deoxy derivatives (10), in the carbonmonoxy derivatives, a remarkable effect (red shift) was observed for the ␤V(E11)T mutant, whereas the recombinant wild-type proteins and the ␣V(E11)T mutant exhibited almost the same behavior as HbA. This shows that, for the CO derivatives, the Val(E11)T substitution in the ␤-chain considerably alters the local electric field at the chromophore (and therefore the pure electronic transi- Increased ␣/␤-Heme Pocket Polarity Dynamic/Functional Effectstion frequency 0 ), whereas the effect is smaller for the ␣-chain mutation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In deoxy-HbA, Val ␤E11 overlaps the ligand-binding site and is considered to play a key role in controlling the oxygen affinity (40). It has also been shown that the replacement of Val ␤E11 with Ile affects the kinetic parameters of oxygen binding (41), because of the larger sec-butyl group that sterically hinders access of ligands to the heme iron. The contact surface area between the ␤-heme and Ile(E11) is 59 Å 2 in T. newnesi Hb C (displaying the substitution Val ␤E11 3 Ile ␤E11 at the distal side of the heme pocket), whereas it is 50 Å 2 in Trematomus bernacchii Hb, which has Val (42).…”
Section: Zoarcoid Perciformsmentioning
confidence: 99%